Effects of anaerobic exercise training on human function based on multiple linear regression - Xiao, Haiting; Peng, Kun; Sun, Liman; Pan, Feng (Frontiers in Physics, 2023)
In recent years, with the continuous enhancement of people’s fitness awareness, more and more people are doing anaerobic exercise training. Although anaerobic exercise training can improve physical fitness, people also have some problems in anaerobic exercise training due to the lack of necessary exercise training guidance. Therefore, in order to give full play to the role of anaerobic exercise training and enhance human body functions, this paper studies the effects of anaerobic exercise training and anaerobic exercise training on human body functions based on multiple linear regression analysis (MLR). This paper proposes an anaerobic exercise training model based on MLR, and conducts research experiments from seven aspects including exercise capacity, immunity, and cardiovascular function. The experimental results show that the MLR-based anaerobic exercise training mode can improve exercise capacity by 5.48%, immunity by 3.08%, and cardiovascular function by 4.31%.